Genetic disruption of the inflammasome adaptor ASC has minimal impact on the pathogenesis of Duchenne muscular dystrophy in mdx Mice - Lau, Yeh Siang (Life Sci, 2020)
AIM: Up-regulation of inflammasome proteins was reported in dystrophin-deficient muscles. However, it remains to be determined whether inflammasome activation plays a role in the pathogenesis of Duchenne muscular dystrophy. This study was therefore set out to investigate whether genetic disruption of the inflammasome pathway impacts the disease progression in mdx mice. MAIN METHODS: Mice deficient in both dystrophin and ASC (encoded by Pycard [PYD And CARD Domain Containing]) were generated. The impact of ASC deficiency on muscular dystrophy of mdx mice were assessed by measurements of serum cytokines, Western blot, real-time PCR and histopathological staining. KEY FINDINGS: The pro-inflammatory cytokines such as TNF-α, IL-6, KC/GRO and IL-10 were markedly increased in the sera of 8-week-old mdx mice compared to WT. Western blotting showed that P2X7, caspase-1, ASC and IL-18 were upregulated. Disruption of ASC and dystrophin expression in the mdx/ASC(−/−) mice was verified by Western blot analysis. Histopathological analysis did not find significant alterations in the muscular dystrophy phenotype in mdx/ASC(−/−) mice as compared to mdx mice. SIGNIFICANCE: Taken together, our results show that disruption of the central adaptor ASC of the inflammasome is insufficient to alleviate muscular dystrophy phenotype in mdx mice.